Allegorien des Politischen - Deutschmann, Peter (2017)
The monograph explores, by means of a diachronic overview, the ways in which historical dramas in Czech literature changed between the outset of the Czech national rebirth and the Republic of Czechoslovakia between the wars. The investigation is based on the fundamental notion that allegorical structures in historical dramas refer to the time at which a given work is created. A general overview on theoretical and historical aspect of Historical Drama leads into the study.